Large anterior congenital urethral diverticulum in an infant: a case report - Hassan, Mohammed A.; Bapir, Rawa; Aghaways, Ismaeil; Hama, Nali H.; Raheem, Mohammed Fahad; Sabr, Wirya N.; Mohammed, Bilal A.; Kareem, Honar Othman; Mustafa, Ayman M.; Kakamad, Fahmi H. (Frontiers in Surgery, 2024)
IntroductionA Urethral diverticulum can be defined as sac-like dilation lined with epithelial tissue, which may be congenital or acquired. It usually develops in the penoscrotal angle region but can also be observed in the penile urethra. It usually occurs in female teenagers. This report aims to discuss a male infant with a large urethral diverticulum.Case presentationA 5-month-old male presented to the urological department at Sulaimani Teaching Hospital with a penile swelling that had been noticeable since birth. Clinical examination revealed a ventral cystic penile shaft swelling, which would fill with fluid during urination. A urethrocystoscopy was performed and showed a wide cystic ventral diverticulum. Diverticulectomy was performed as a surgical approach to remove the diverticulum.DiscussionCongenital anterior urethral diverticulum is an uncommon condition that typically begins in early life. It can manifest with various symptoms, like recurrent infections of the urinary tract, painful urination, and post-void urine dribbling. Diagnosis involves imaging, with urethrocystoscopy, to rule out other potential diagnoses. Different surgical techniques exist that show promising results in preventing recurrence. The current case involved diverticulectomy and multi-layered wound closure with a dartos flap.ConclusionLarge anterior diverticulum in early infancy is rare but possible; operation is the preferred intervention method.